The Effect of Stocking Density on Growth of The Grouper (Cromileptes altivelis) Cages System in Banda Waters, Maluku - Aditya Putra Basir; Dinawanti Larae (Universitas Tidar, 2019)
The Grouper (Cromileptes altivelis) is a species of fish that has a significant economic value which selling price is quite high. High fish prices encourage fisherman to exploit continiously. This will lead to an over fishing. Grouper farming has a bright opportunity in the future but it is still facing difficulties in rearing. So some of the parameters should be focused. One of them is the stocking density which closely related to the area of rearing. The purpose of this study was to determine the growth rate of fish grouper wich different stocking density tratments in floating net cages. The method used in tratments and 3 replications. There were 9 cages used with size used 1x1x1,5 m. and mesh size of 0,5 inches as rearing place. Initial weight of grouper fish were observed at the time of stocking density 5 grams. Condition of aquatic environments is suitable for grouper growth except for the low flow velocity. The rearing of grouper fish with different stocking density treatments showed a significant different. The highest growth was represented by treatment A wich was 25,40 grams, followed by treatment B with 23,26 grams and treatment C was 22,10 grams.